Alpha-linolenic acid enhances maturation and developmental competence via regulation of glutathione, cAMP and fatty acid accumulation during in vitro maturation of porcine oocytes - Ye-Eun Jeon; Yong Hwangbo; Sun-Young Kim; Choon-Keun Park (The Korean Society of Animal Reproduction and Biotechnology, 2020)
The aim of present study was to investigate regulatory mechanism of alpha-linolenic acid (ALA) during in vitro maturation (IVM) on nuclear and cytoplasmic maturation of porcine oocytes. Basically, immature cumulus-oocyte complexes (COCs) were incubated for 22 h in IVM-I to which hormone was added, and then further incubated for 22 h in IVM-II without hormone. As a result, relative cumulus expansion was increased at 22 h after IVM and it was enhanced by treatment of ALA compared with control group (p < 0.05). During IVM process within 22 h, cAMP level in oocytes was decreased at 6 h (p < 0.05) and it was recovered at 12 h in ALA-treated group, while oocytes in control group recovered cAMP level at 22 h. In cumulus cells, it was reduced in all time point (p < 0.05) and ALA did not affect. Treatment of ALA enhanced metaphase-I (MI) and MII population of oocytes compared with oocytes in control group at 22 and 44 h, respectively (p < 0.05). Intracellular GSH levels in ALA group was increased at 22 and 44 h after IVM (p < 0.05), whereas it was increased in control group at 44 h after IVM (p < 0.05). In particular, the GSH in ALA-treated oocytes during 22 h of IVM was higher than control group at 22 h (p < 0.05). Lipid amount in oocytes from ALA group was higher than control group (p < 0.05). Treatment of ALA did not influence to absorption of glucose from medium. Cleavage and blastocyst formation of ALA-treated oocytes were enhanced compared with control group (p < 0.05). These findings suggest that supplementation of ALA could improve oocyte maturation and development competence through increasing GSH synthesis, lipid storage, and regulation of cAMP accumulation during early 22 h of IVM, and these might be mediated by cumulus expansion.